OCEAN CURRENT CIRCULATION MODEL AROUND GRESIK COASTAL AREA, EAST JAVA - IQBAL FAUZAN MUHAMMAD (NIM : 12909020),
Gresik is a city located in north coast of East Java, with Madura Strait as east border and Java Sea as north border. As a coastal city, Gresik has a big port which is used for industry and trade either for national or regional scale. Using the sea for industry, electricity, and transportation, knowledge about ocean current dynamics and characteristics of the sea around Gresik is needed. That is why the knowledge about sea around Gresik characteristics is a basic needed because the characteristics can determine the process of using sea for industry, electricity and transportation. In this study, MIKE21 is used for simulating hydrodynamics around Gresik. In this simulation, the ocean current movement is generated by tide as north and east open boundaries which is simulated in January and July 2014. The ocean current produced by simulation can be used for analysing the ocean current pattern during west moonson wind seasonal period or east moonson wind seasonal period. The simulation indicate that the verification results show conformity of simulation and field measurement data with 0,372 m different in RMSE. Ocean current pattern does not change during west moonson wind seasonal period or east moonson wind seasonal period no matter it is spring or neap tides condition (when it is flood the current moves from east to north and the current moves from north to east when it is ebb), just the magnitude of the ocean current affected by moonsonal wind variability. If the ocean current moves along the moonsonal wind season, the ocean current is accelerated and if the ocean current moves against the moonsonal wind season, the ocean current is deaccelerated because of wind friction. Toward spring flood, the average ocean current speed is 0,53 m/s in west moonsonal period and 0,82 m/s in east moonsonal period, while toward spring ebb is 0,73 m/s in west moonsonal period and 0,66 m/s in east moonsonal period.